Kekuasaan Peradilan Militer Mengadili Warga Sipil Dalam Tinjauan Hukum Tata Negara Darurat - Kurniawan, Denis (Jurnal Hukum & Pembangunan, 2022)
Abstract Military Courts in general are courts devoted to dealing with cases of military soldiers, both concerning criminal matters, military administration, and claims for compensation as a result of criminal offenses. The special nature of military justice is due to the fact that military soldiers have different traditions from civil society regarding the existence of military discipline in their activities, and there are acts that are only known within the military environment, but are not generally applicable. However, a military court in an emergency situation that threatens to be projected as the last court, if the existing judiciary is to handle the interests of civil society, does not have a function in exercising its authority. This research is a normative legal research using a conceptual approach, which relies on the method of literature study or documentation in finding related data and answering research questions. In normal situations, military courts can try civilians who have the same status as "soldiers", as well as civilians who work for the armed forces and hold military secrets, based on a decision from the Military Commander. Military courts in dangerous conditions can be justified as a last resort if the existing judiciary does not carry out its functions, this is done to always be oriented towards upholding the rule of law in any condition and situation.